1994
DOI: 10.1128/iai.62.7.2761-2772.1994
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor alpha has a protective role in a murine model of systemic candidiasis

Abstract: The role of tumor necrosis factor alpha (TNF-a) in host defense against systemic Candida albicans infection was evaluated in a murine model of systemic candidiasis in which uniform death occurred between 5 and 6 days after infection. TNF-a was first detected at 16 h postinfection and progressively increased thereafter. Peak levels (700 to 900 pg/ml) were measured in mice near death. Administration of 0.5 to 1.0 mg of polyclonal immunoglobulin G (IgG) TNF-oa antibody (TNF-ax Ab) to mice 2 h preinfection neutral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0
9

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(46 citation statements)
references
References 45 publications
4
33
0
9
Order By: Relevance
“…33,34 Thus, the importance of NF-jB activity in C. albicans infection is based on its capacity to induce anticandidal cytokines such as TNF-a, IL-1 and granulocyte colony-stimulating factor. [35][36][37] Among these cytokines, we have found that TNF-a is the key effectors molecule in protection against C. albicans. 12,13 Our unpublished recent finding showing that non-pathogenic C. albicans became pathogenic in TNF-a knockout mice, further establishes the importance of this cytokine in C. albicans clearance.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 Thus, the importance of NF-jB activity in C. albicans infection is based on its capacity to induce anticandidal cytokines such as TNF-a, IL-1 and granulocyte colony-stimulating factor. [35][36][37] Among these cytokines, we have found that TNF-a is the key effectors molecule in protection against C. albicans. 12,13 Our unpublished recent finding showing that non-pathogenic C. albicans became pathogenic in TNF-a knockout mice, further establishes the importance of this cytokine in C. albicans clearance.…”
Section: Discussionmentioning
confidence: 99%
“…The pro-in£ammatory cytokine tumor necrosis factor-K (TNFK) is also induced by Candida mannoproteins in vitro [14]. Its requirement for the host defense has become clear from experiments in which treatment of mice with monoclonal antibodies against TNFK enhances the mortality to experimental disseminated candidiasis [15,22]. Likewise, treatment with pharmacological inhibitors of TNFK production leads to enhanced mortality and increased outgrowth of C. albicans during disseminated candidiasis in mice [23].…”
Section: Cytokines and The Recruitment Of Neutrophils At The Site Of mentioning
confidence: 99%
“…The role of TNF-a in this infection was further demonstrated in experiments using anti-TNF-a antibody; the administration of the antibody markedly reduced the survival rate. Louie et al [25] described that the administration of TNF-a antibody in a murine model of systemic candidiasis neutralized serum TNF-a, shortened survival, and increased fungal colony counts in the spleen, kidney, liver and lung. Nagai et al [20] also reported that TNF-a exhibits a protective role in invasive aspergillosis.…”
mentioning
confidence: 99%